2018
DOI: 10.1039/c8ta01064a
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous solution-processed off-stoichiometric Cu–In–S QDs and their application in quantum dot-sensitized solar cells

Abstract: Off-stoichiometric CuInS2 quantum dots (CuInS2, a mixture of In2S3/CuInS2, and a Mn-doped mixture of In2S3/CuInS2) were prepared in a one-pot reaction, and the corresponding sensitized solar cells exhibit promising photovoltaic performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 62 publications
1
21
0
1
Order By: Relevance
“…The integral J SC values for CuS, NiS, and PbS were 20.42, 18.83, and 18.64, respectively, and followed the trend extracted from J–V curves. The estimated J SC values are lower than the measured values from J–V curves due to the lower light intensities used in the IPCE measurement, the effect of high chopping frequency on the IPCE spectrum, and the absence of bias light . As regards the NiS and PbS based QDSSCs, the responses are comparable with a slightly higher value for NiS CEs that is also consistent with the variation in their PCEs.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The integral J SC values for CuS, NiS, and PbS were 20.42, 18.83, and 18.64, respectively, and followed the trend extracted from J–V curves. The estimated J SC values are lower than the measured values from J–V curves due to the lower light intensities used in the IPCE measurement, the effect of high chopping frequency on the IPCE spectrum, and the absence of bias light . As regards the NiS and PbS based QDSSCs, the responses are comparable with a slightly higher value for NiS CEs that is also consistent with the variation in their PCEs.…”
Section: Resultssupporting
confidence: 57%
“…The clear lattice pattern features crystalline nature of CuInS 2 /In 2 S 3 with the two crystal structures of CuInS 2 and In 2 S 3 having the lattice spacing of 0.319 and 0.164 nm, respectively. In our previous work, we reported the synthesis and characterization of CuInS 2 /In 2 S 3 photoelectrode and demonstrated that the In 2 S 3 buffer layer decreases the recombination losses at CuInS 2 and TiO 2 junction . Introduction of this layer also benefited the band alignment at the TiO 2 /CuInS 2 interface.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…198,211,216,[243][244][245][246][247][248] Up to date, the reported highest PCE with use of aqueous QD sensitizer under the irradiation of one full sun light is 8.0%, and a PCE of 8.15% was also obtained but under light intensity of 30 mW cm -2 . 249,250 It is noted that the aqueous QD sensitizers were mostly concentrated on CuInS2, and CdTe based QDs due to the relatively matured aqueous synthesis methods for these two kinds of QDs. A variety of binary QDs, such as InP, 95,209 InAs, 96 CdS, 146,202,251,252 CdSe, 99,100,110,200,203 CdTe, 206,253 PbS, 127,207,213,[254][255][256][257][258][259] Ag2S, 169,210,[260][261][262] etc.…”
Section: Qds Sensitizersmentioning
confidence: 99%